PENGARUH MOTIVASI BELAJAR, KECERDASAN EMOSIONAL DAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PENGANTAR EKONOMI DAN BISNIS SISWA KELAS X SMK ARDJUNA 02 ARJOSARI TAHUN AJARAN 2015/2016 - Anggun Yulia Rina Putri; Prih Hardinto; Mardono Mardono (Jurnal Pendidikan Ekonomi, 2016)
In order to improve student learning outcomes of class X SMK Ardjuna 02 Arjosari on Introduction Economics and Business subjects one of them is measured through learning motivation, emotional intelligence and family environment. This study aims to determine the effect of learning motivation, emotional intelligence and family environment on learning outcomes on Introductory Economics and Business subjects. The method used is quantitative explanation with population number 77 with sample using proportional random sampling counted 65 students. The result of hypothesis testing shows the significance of t test of learning motivation is 0,003, emotional intelligence 0,001 and family environment 0,004. While the f test of 0.000 on the learning outcomes. So there is a significant influence between learning motivation, emotional intelligence and family environment on learning outcomes on Introductory Economics and Business subjects.